Penentuan Kelayakan Tahanan Isolasi Pada Transformator 60 MVA Di Gardu Induk 150 kV Tegal Dengan Menggunakan Indeks Polarisasi, Tangen Delta, Dan Breakdown Voltage - Robbani, Muhamad Firdaus; Nugroho, Dedi; Gunawan, Gunawan (Universitas Semarang, 2020)
A power transformer is electrical power equipment that works to transmit power or electrical power from high voltage to low voltage or on the contrary. In the operation of distributing electricity, the transformer can be said to be the heart of transmission and distribution. In this condition, a transformer is expected to operate optimally according to its function.. If the isolation state of the transformer deteriorates, it can have an impact on operating failure and the most fatal of which is that the transformer is damaged which can cause disturbances in the electrical system. To overcome this, it is necessary to analyze the isolation resistance.This study analyzes the isolation resistance on a transformer using the polarization index, tangent delta and oil breakdown voltage methods to determine the quality of the isolation on the transformer. This study took data at the 150 Kv substation Tegal. The data used include polarization index test data, tangent delta data, bottom oil breakdown voltage test data, and OLTC oil. After the data is obtained, then calculations and analyzes are carried out to obtain accurate results.The test results at the 150 Kv substation Tegal showed the polarization index value with the lowest IP of 1.26 in the primary-ground section and the highest IP of 1.97 in the primary-secondary section is still in good condition. The results of the tangent delta test are still in good condition, only in the CHT mode experienced a negative delta tan deterioration of 0.07%. The result of the average oil test is still suitable for use with 69.9 Kv of bottom oil and 53.3 Kv of OLTC oil.